Outdoor Physical Activity with Cognitively Engaging Tasks May Affect Students’ Creative Thinking: A Pilot Study for an Innovative Didactic Approach in Educational Contexts - Francesca Latino (Formazione & Insegnamento, 2022)
Although creative thinking is described as an important factor of student’s intellectual development and it is classified as one of the most valuable twenty-first century competences to achieve success and remarkable progress in academic, professional, personal, and social life, a limited amount of published research has explored how outdoor physical activity with cognitively engaging tasks may affects it. Therefore, the purpose of the present study is to explore the relationship between outdoor physical activity and creativity among students. 120 students (aged 13-14) participated in 12-week of either an outdoor physical activity program (60'/ 2 days per week) or a regular and easy-to-perform physical education class (60'/ 2 days per week). The findings from the present study support the idea that outdoor physical activity with cognitively engaging tasks may promote the development of students’ creative thinking.